KORELASI DAN ANALISIS LINTAS ANTARA KARAKTER AGRONOMI DENGAN HASIL PADA PINANG EMAS (ARECA CATECHU L.) [CORRELATION AND PATH ANALYSIS BETWEEN AGRONOMY CHARACTERS OF PINANG EMAS (ARECA CATECHU L.) WITH YIELD ] - Miftahorrachman, nFN; Mawardi, Sukmawati; Maskromo, Ismail (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
Pinang Emas is a new high yielding variety of arecanut, is resulted from positive mass selection of arecanuts population in Kota Kotamobagu, North Sulawesi Province. The study was purposing to estimate the correlation between vegetative, generative and fruit component characters to yield of Pinang Emas. The research was conducted in The Kayuwatu Experimental Garden, Indonesia Coconut Palm Research Institue, North Sulwesi, from January to December 2018. Path analysis of 21 characters using formula of Singh and Chaudary. The results of simple correlation analysis produce 25 relationships, most of which are relationships among the fruit component characters and there is no correlation with the number of fruits per bunch (JBT). The results of a simple correlation analysis resulted in 25 relationships, most of which were relationships between fruit component characters and there was no correlation with the number of fruits per bunch (JBT). Path analysis of six characters of fruit component showed only character of polar length of unhusked fruit (PPBTS) has direct effect to weight of fruit with value of r= 0.56 and indirect effect of BBBTS through PPBTS caharacter. The benefit of this research is that the character of PPBTS can be used as a selection criterion for the improvement of the production of Pinang Emas.ABSTRAKPinang Emas merupakan varietas unggul baru pinang, sebagai hasil seleksi massa positif dari tetua yang berasal dari Kota Kotamobagu, Sulawesi Utara. Penelitian ini bertujuan untuk mengetahui korelasi antara karakter vegetatif, generatif dan komponen buah dengan produksi buah varietas Pinang Emas. Penelitian ini dilaksanakan di Kebun Percobaan Kayuwatu, Balai Penelitian Tanaman Palma, Sulawesi Utara, mulai bulan Januari sampai Desember 2018. Analisa sidik lintas 21 karakter vegetatif, generatif serta komponen buah terhadap karakter jumlah buah per tandan menggunakan rumus dari Singh dan Chaudary. Hasil analisis korelasi sederhana menghasilkan 25 hubungan, sebagian besar adalah hubungan antar karakter komponen buah dan tidak terdapat korelasi dengan jumlah buah per tandan (JBT). Hasil analisis sidik lintas tujuh karakter komponen buah, hanya karakter panjang polar buah tanpa sabut (PPBTS) yang berpengaruh langsung terhadap berat buah utuh (BBU) dengan nilai r=0.56, dan pengaruh tidak langsung karakter BBBPTS melalui karakter PPBTS. Manfaat penelitian ini adalah karakter PPBTS dapat dijadikan kriteria seleksi untuk perbaikan produksi Pinang Emas.